Harnessing Ocean Alkalinity Enhancement (OAE) for CO2 Decomposition and Renewable Energy Production : The AODOP Innovation Towards Net-Zero Emissions 2060 - Jennifer Batami; Nadhif Rafif P; Syafira Dewi (Department of Ocean Engineering, 2024)
As the concentration of carbon dioxide (CO2) in atmosphere increases, carbon emissions entering the oceans have become a significant concern in context climate change studies as stated by the Intergovernmental Panel on Climate Change (IPCC) report, 30% of anthropogenic CO2 emissions are absorbed by the oceans, leading decrease in ocean pH and harmful impacts on marine ecosystems. In order to address this challenge, Ocean Alkalinity Enhancement (OAE) has emerged as a promising strategy. By using calcium carbonate compounds, OAE aims to increase seawater alkalinity and enhance its capacity to decompose CO2. The practical implementation of OAE until now is still under further research. Therefore, the initial stage of this application will be carried out in a storage tank as an initial trial before being applied on a large scale. Furthermore, the results of the OAE process can contribute to production of renewable energy through the implementation of Pressure Retarded Osmosis (PRO) technology, which leverages the salinity gradient between seawater with high alkalinity and freshwater to generate energy. By combining OAE with PRO this approach offers a promising pathway toward a thriving blue future to facilitate the integration of marine ecosystems in achieving sustainability and net-zero emission by 2060.